MULTIWORD-LEXIS AND NON LITERAL USES FOUND IN THE GUARDIAN ARTICLE - Dwi - Wahyuningtyas (Jurnal Bahasa Lingua Scientia, 2022)
In mastering vocabulary, language learners often face some challenges, one of which is the occurrences of multiword-lexis and non-literal uses that consist of polysemy, collocation, phrasal verb, idiom, metaphor, and metonymy. This paper will then analyse multiword-lexis and non-literal uses found in a newspaper, the Guardian. Descriptive qualitative research design was employed in this research. The findings showed that there are two (2) occurrences of polysemy, fifteen (15) occurrences of collocation, nine (9) occurrences of phrasal verb, three (3) occurrences of idiom, two (2) occurrences of metaphor, and two (2) occurrences of metonymy with the total thirty three (39) occurrences. The occurrences of non-literal meaning can be grouped into idiom, metaphor, and metonymy.